1988
DOI: 10.1530/jrf.0.0840393
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic mortality and the uterine environment in first-service lactating dairy cows

Abstract: Embryos were collected non-surgically from the tip of one uterine horn of 23 lactating dairy cows on Day 7 of pregnancy. Embryos were classified on the basis of morphological criteria as normal (n = 12) or abnormal (n = 13). Abnormal embryos were further classified as cleavage stage (n = 9) or morula/blastocyst (n = 4). Cows producing an abnormal embryo did not differ in days post partum at oestrus, age or parity from cows producing a normal embryo. Cows with an abnormal morula/blastocyst also did not differ w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
2

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 7 publications
0
24
1
2
Order By: Relevance
“…However, there are many published reports of fertilization rates in heifers and moderate-yielding dairy cows with estimates varying from 90% to 100% (see review by Diskin and Sreenan, 1980). Data relating to the high-producing dairy cows are rather limited, with only three published reports (Wiebold, 1988;Ryan et al, 1993;Sartori et al, 2002). These latter reports indicate that at least under temperate ambient temperatures, fertilization rates are most likely similar for moderate and high-producing dairy cows.…”
Section: Degree and Timing Of Embryo Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are many published reports of fertilization rates in heifers and moderate-yielding dairy cows with estimates varying from 90% to 100% (see review by Diskin and Sreenan, 1980). Data relating to the high-producing dairy cows are rather limited, with only three published reports (Wiebold, 1988;Ryan et al, 1993;Sartori et al, 2002). These latter reports indicate that at least under temperate ambient temperatures, fertilization rates are most likely similar for moderate and high-producing dairy cows.…”
Section: Degree and Timing Of Embryo Lossmentioning
confidence: 99%
“…There are little data on the extent or timing of early embryo loss in high-producing dairy cows. However, based on morphological criteria, three studies (Wiebold, 1988;Ryan et al, 1993;Sartori et al, 2002) have shown that a high proportion (41% to 67%) of embryos recovered on days 6 to 7 from moderate-to high-producing dairy cows had lower cell numbers or were of a lower quality grade than those from heifers or non-lactating cows.…”
Section: Degree and Timing Of Embryo Lossmentioning
confidence: 99%
“…a). Wiebold (1988) reported that most of the embryonic mortality occurred before day 5 in cows, which was associated with a uterine environment which significantly differed that of cows with normal embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Usually lymphocytes predominate at later stages of infection and in repeaters the chronic inflammatory response would result in elevated lymphocyte concentration in uterine lumen (Babu, 2013). Wiebold (1988) reported that in chronic bacterial infection, the causative bacteria produce certain chemical factors, which inhibit the stimulation of uterine defense mechanism (UDM). The reason for low numbers of leucocytes in a natural infection could be that the prevalent bacteria were either not conductive to cause a sufficient influx of PMN or those PMN degenerated too quickly (Singh et al, 2000).…”
Section: Lymphocytementioning
confidence: 99%
“…Es muy posible que una significante proporción de la reducción de la fertilidad en la población de vacas sea atribuible a una falla en la función lútea materna y consecuentemente un inadecuado ambiente uterino dependiente de la progesterona (Wiebold 1988). Diversos estudios han mostrado resultados controversiales en cuanto al efecto del estrés calórico sobre los niveles de progesterona durante el diestro, ya que algunos han reportado incrementos (Vaught y col 1977), reducciones (Wolfenson y col 1988) o ningún efecto (Wise y col 1988), como fue el caso del presente estudio, aún en el tratamiento donde se suplementó P 4 .…”
Section: Discussionunclassified